On Pitchfork Domination Number of Corona of Some Graphs - Barnido, Kris D.; Espinola, Stephanie O. (Communications in Mathematics and Applications, 2024)
A dominating set \(D\) of \(V\) is called a pitchfork dominating set if every vertex in it dominates at least \(j\) vertices and at most \(k\) vertices of \(V-D\), for any non-negative integers \(j\) and \(k\). The pitchfork domination number of \(G\), denoted by \(γ_pf (G)\) is the minimum cardinality over all pitchfork dominating sets in \(G\). In this paper, the pitchfork domination when \(j=1\) and \(k=2\) are applied to the corona of some graphs: \(G ° C_m\), \(G ° K_1,n\), \(G ° K_p,q\), \(G ° B_2,k\) and \(G ° F_2,k\). In relation to getting new results of the corona of the mentioned graphs, we also generate results of pitchfork domination number of \(P_2+K_n\), \(K_1 + K_p,q\), \(B_2,k\), \(F_2,k\) and \(K_1 + F_2,k\).